Changes in the TCRβ Repertoire and Tumor Immune Signature From a Cutaneous Melanoma Patient Immunized With the CSF-470 Vaccine: A Case Report - Mariana Aris; Alicia Inés Bravo; María Betina Pampena; Paula Alejandra Blanco; Ibel Carri; Daniel Koile; Patricio Yankilevich; Estrella Mariel Levy; María Marcela Barrio; José Mordoh; José Mordoh; José Mordoh (Frontiers in Immunology, 2018)
The allogeneic therapeutic vaccine CSF-470 has demonstrated a significant benefit over medium-dose IFNα2b in the distant metastasis-free survival for stages IIB–IIC–III cutaneous melanoma patients in a randomized phase II/III clinical trial (CASVAC-0401, NCT01729663). At the end of the 2-year CSF-470 immunization protocol, patient #006 developed several lung and one subcutaneous melanoma metastases; this later was excised. In this report, we analyzed the changes throughout vaccination of immune populations in blood and in the tumor tissue, with special focus on the T-cell repertoire. Immunohistochemistry revealed a marked increase in CD8+, CD4+, and CD20+ lymphocytes infiltrating the metastasis relative to the primary tumor. Lymphocytes were firmly attached to dying-tumor cells containing Granzyme-B granules. Whole-exon sequencing assessment indicated a moderate-to-high tumor mutational burden, with BRAFV600E as the main oncogenic driver. Mutational signature presented large numbers of mutations at dipyrimidines, typical of melanoma. Relevant tumor and immune-related genes from the subcutaneous metastasis were addressed by RNA-Seq analysis, revealing expression of typical melanoma antigens and proliferative tumor-related genes. Stimulatory and inhibitory immune transcripts were detected as well as evidence of active T-cell effector function. Peripheral blood monitoring revealed an increase in CD4+ and CD8+ cells by the end of the immunization protocol. By CDR3-T-cell receptor β (TCRβ) sequencing, generation of new clones and an increase in oligoclonality was observed in the peripheral T-cells immune repertoire throughout immunization. A shift, with the expansion of selected preexisting and newly arising clones with reduction of others, was detected in blood. In tumor-infiltrating lymphocytes, prevalent clones (50%) were both new and preexisting that were expanded in blood following CSF-470 immunization. These clones persisted in time, since 2 years after completing the immunization, 51% of the clones present in the metastasis were still detected in blood. This is the first report of the modulation of the TCRβ repertoire from a melanoma patient immunized with the CSF-470 vaccine. After immunization, the changes observed in peripheral immune populations as well as in the tumor compartment suggest that the vaccine can induce an antitumor adaptive immune repertoire that can reach tumor lesions and persists in blood for at least 2 years.